2001
DOI: 10.1021/bi0022700
|View full text |Cite
|
Sign up to set email alerts
|

Complete Amino Acid Sequence of Kaouthiagin, a Novel Cobra Venom Metalloproteinase with Two Disintegrin-like Sequences

Abstract: The primary structure of kaouthiagin, a metalloproteinase from the venom of the cobra snake Naja kaouthia which specifically cleaves human von Willebrand factor (VWF), was determined by amino acid sequencing. Kaouthiagin is composed of 401 amino acid residues and one Asn-linked sugar chain. The sequence is highly similar to those of high-molecular mass snake venom metalloproteinases from viperid and crotalid venoms comprised of metalloproteinase, disintegrin-like, and Cys-rich domains. The metalloproteinase do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…Berythractivase presents three potential N-glycosylation sites in its amino acid sequence ( Figure 6). Some snake-venom metalloproteinases have also been shown to be glycosylated [43,44]. Analysis of the cDNA sequence revealed that berythractivase is a member of the P-III class of the metalloproteinase protein family.…”
Section: Discussionmentioning
confidence: 99%
“…Berythractivase presents three potential N-glycosylation sites in its amino acid sequence ( Figure 6). Some snake-venom metalloproteinases have also been shown to be glycosylated [43,44]. Analysis of the cDNA sequence revealed that berythractivase is a member of the P-III class of the metalloproteinase protein family.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there are three PIII class SVMPs, HR1B, from the venom of Trimeresurus flavoviridis [50], BjussuMP_I, from Bothrops jararacussu [51], and kaouthiagin, from Naja kaouthia [52], that have the integrin‐binding motifs KGD or RGD in their cysteine‐rich domains (Fig. 6).…”
Section: Structural Features Of the Svmps That Contribute To Venom Comentioning
confidence: 99%
“…HR1B CRAAES ECD IPESC [61,99] Ht -e CR VS MVD RNDDTC [100] Jararhagi n CRASMS ECD PAEHC [60] Jararhagi n-C CRASMS ECD PAEHC [60,65] Kaouthiagin CRA AKHDCD LPELC [101] Mocarhagi n CRA AKNDCD FPELC AAM51550*…”
Section: The Disintegrin-like Domain Of Snake Venom Metalloproteinasementioning
confidence: 99%